Regenerative therapy for hypothyroidism: Mechanisms and possibilities. (15th April 2017) - Hollenberg, Anthony N.; Choi, Jinyoung; Serra, Maria; Kotton, Darrell N.
Abstract: The ability to derive functional thyroid follicular cells from embryonic stem cells (ESCs) or induced pluripotent stem cells (iPSCs) would provide potential therapeutic benefit for patients with congenital or post-surgical hypothyroidism. Furthermore, understanding the process by which thyroid follicular cells develop will also provide great insight into the key steps that regulate the development of other tissues derived from endoderm. Here we review the advances in our understanding of the process of thyroid follicular cell development including the creation of two models that have allowed for the rescue of hypothyroid mouse recipients through the transplantation of thyroid follicular cells derived from mouse ESCs. Rapid progress in the field suggests that the same success should be achievable with human ESCs or iPSCs in the near future. Additionally, the availability of ESC or iPSC-derived thyroid follicular cell models will provide ideal systems to explore how genetic mutations, drugs or illness impact thyroid function in a cell-autonomous fashion.